2015
DOI: 10.4155/bio.15.159
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalysis of Ibrutinib and its Active Metabolite in Human Plasma: Selectivity Issue, Impact Assessment and Resolution

Abstract: Ronald de Vries graduated in Organic and Analytical Chemistry at the Free University of Amsterdam, The Netherlands. After working in a Contract Laboratory (CRO) for 7 years, he joined Janssen R&D in 1998. At Janssen R&D, Belgium, Ronald worked in the bioanalytical department that supports both clinical and nonclinical bioanalysis. In this department he had several roles, such as providing the bioanalytical support for various drug development programs and leading the method establishment group. He has done num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The lower limit of quantitation (LLOQ) and the precision (%CV) of the assay in human plasma were 0.5 ng/mL and ,11%, respectively. 12 Pharmacokinetic data analysis. Plasma ibrutinib and PCI-45227 concentration-time profiles were initially inspected on a log-linear plot and analyzed using noncompartmental methods (WinNonLn Pro software).…”
Section: Methodsmentioning
confidence: 99%
“…The lower limit of quantitation (LLOQ) and the precision (%CV) of the assay in human plasma were 0.5 ng/mL and ,11%, respectively. 12 Pharmacokinetic data analysis. Plasma ibrutinib and PCI-45227 concentration-time profiles were initially inspected on a log-linear plot and analyzed using noncompartmental methods (WinNonLn Pro software).…”
Section: Methodsmentioning
confidence: 99%
“…However, the optimization of MRM is rather time consuming and requires a skilled technician, as cross-talk, adducts and non-specific CID-transitions have to be accounted for [119]. Co-eluting matrix-components with a very close m/z value to that of the analyzed parent drug can also be problematic in SRM acquisition [72,120,121]. Due to its selectivity, with SRM acquisition of additional information like degradation products or adducts of the analytes of interest is lost.…”
Section: Orbitrapmentioning
confidence: 98%
“…Next to effects on ionization, isobaric interferences can prove problematic as well. Such an example can be taken from the analysis of ibrutinib, where in plasma samples from a clinical study in hepatically impaired subjects, taurocholic acid showed interference with the internal standard of the active metabolite dihydrodiol-ibrutinib [72]. Some TKIs require specific conditions when handling, such as sunitinib, where exposure of the samples to light causes isomerization, and all sample preparation must be done in light-protected conditions [69].…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations